Spiritual Leadership of School Administrators in the Digital Age - Chottantitarasagul, Khanchai; Wannawan, Panithan; Wannawan, Kethanok; Poopayang, Piangkhae; Sukserm, Pennapha (Dhammathas Academic Journal, 2023)
Thai education management has always been evolving. It may be due to the internal and external factors causing society to change. As a result, Thai education must be adapted to modernization and keep pace with changes to achieve development that is on par with other civilized countries. Therefore, spiritual leadership that can build credibility, faith, vision, and motivation, raise awareness, and value performance by developing positive organizational potential is a new paradigm that can be promoted and supported in the organization to achieve its objectives effectively. Thus, it influences to drive Thai education quality. Spiritual Leadership of School Administrators in the Digital Age is the era of applying the technology of the modern world that is full of the speed of change together with good attributes, knowledge, ability, skills, competencies, morality, and ethics in the administration in order to move towards to the potential development, quality, and the highest efficiency of the changes that occur. The 21st century School administrators must therefore focus on the administration that can lead the organization to its objectives, achieve the goals or vision set with quality and also increase the competency in developing humans to have the capability for sustainable development. Building spiritual leadership in schools is very important in the digital age because it helps school personnel to love, trust, and cooperate in enhancing knowledge together. Dedicating energy to various operations to achieve the goals, strategies, and visions that benefit the school, society, and nation.